Enhancing the innovation of small and medium enterprises in food manufacturing through Triple Helix Agents - Ueasangkomsate, Pittawat; Jangkot, Alisara (Kasetsart Journal of Social Sciences, 2017)
This research aimed to enhance the innovation of Thai small and medium enterprises (SMEs) in food manufacturing through Triple Helix Agents, namely, the university, industry, and government sectors. For the study 87 responses were received from a questionnaire collecting data regarding SME collaboration with Triple Helix Agents and innovation performance based on convenience sampling. The majority of the sample were fruit and vegetable processing manufacturers followed by meat and ﬁsh/aquatic animal processing manufacturers. SME collaboration with the industry sector was at the highest level when compared with the university and government sectors, respectively. Conﬁrmatory factor analysis was applied to construct the measurement using PLS-SEM, and then multiple regression was applied to quantify the relationship between the identiﬁed factors. The statistical analysis provided insights into the inﬂuence of Triple Helix Agents on product and process innovation. The ﬁndings indicated that SME collaboration with the industry sector had a positive effect on enhancing the innovation of Thai food manufacturing SMEs at the .05 signiﬁcance level and the government sector also had a positive inﬂuence at the .05 signiﬁcance level. The study contributes to explaining the level of interactions among Triple Helix Agents in the SME context. The results revealed the potential beneﬁts for SMEs in emerging economies when collaborating with Triple Helix Agents in terms of enhancing their innovation performance.